2020
DOI: 10.1002/ange.202008759
|View full text |Cite
|
Sign up to set email alerts
|

Axial Modification of Cobalt Complexes on Heterogeneous Surface with Enhanced Electron Transfer for Carbon Dioxide Reduction

Abstract: Efficient electron communication between molecular catalyst and support is critical for heterogeneous molecular electrocatalysis and yet it is often overlooked during the catalyst design. Taking CO 2 electro-reduction on tetraphenylporphyrin cobalt (PCo) immobilized onto graphene as an example,w ed emonstrate that adding ar elay molecule improves the interfacial electron communication. While the directly immobilized PCo on graphene exhibits relatively poor electron communications,i ti sf ound that diphenyl sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…The renewable electricity-driven reduction of carbon dioxide (CO 2 RR) represents a promising approach to generate sustainable fuels and chemicals that are currently manufactured using energy-intensive methods. It is already established that CO 2 can be exclusively converted into CO and formic acid, but the generation of further reduced products, especially multicarbon (C 2+ ) oxygenates and hydrocarbons (e.g., ethylene, ethanol) with higher energy densities, is more desirable in terms of economic efficiency and industrial applications. For the formation of C 2+ products, the C–C coupling step is crucial yet highly sensitive to the catalyst, which is mainly achieved on Cu-based catalysts. Various nanostructured Cu catalysts have been explored to promote the formation of C 2+ products, but it still suffers from high overpotential, poor C 2+ selectivity, and serious hydrogen evolution reaction (HER). , To this end, bonding C atoms of CO 2 with other available heteroatoms (e.g., N, S) in light of the formation mechanism for C 2+ species is an alternative strategy to produce value-added products which is highly beneficial for expanding the application of CO 2 RR. …”
mentioning
confidence: 99%
“…The renewable electricity-driven reduction of carbon dioxide (CO 2 RR) represents a promising approach to generate sustainable fuels and chemicals that are currently manufactured using energy-intensive methods. It is already established that CO 2 can be exclusively converted into CO and formic acid, but the generation of further reduced products, especially multicarbon (C 2+ ) oxygenates and hydrocarbons (e.g., ethylene, ethanol) with higher energy densities, is more desirable in terms of economic efficiency and industrial applications. For the formation of C 2+ products, the C–C coupling step is crucial yet highly sensitive to the catalyst, which is mainly achieved on Cu-based catalysts. Various nanostructured Cu catalysts have been explored to promote the formation of C 2+ products, but it still suffers from high overpotential, poor C 2+ selectivity, and serious hydrogen evolution reaction (HER). , To this end, bonding C atoms of CO 2 with other available heteroatoms (e.g., N, S) in light of the formation mechanism for C 2+ species is an alternative strategy to produce value-added products which is highly beneficial for expanding the application of CO 2 RR. …”
mentioning
confidence: 99%
“…Meanwhile, besides the conventional outersphere electron transfer by the random collision between PS and catalyst in a mixture, the intermolecular electron transfer can be additionally facilitated in a manner of inner-sphere electron transfer (ISET) via the coordinative interaction 36 as either a stable adduct or a transition state, potentially overcoming the diffusion limit 37 . Such coordinative interaction between PS and catalyst has been utilized in the molecular systems for hydrogen evolution 31,33,[38][39][40] or immobilizing molecular catalysts on heterogeneous materials [41][42][43][44] . The coordinative interaction between tertiary amine as potential sacrificial reagent and planar PSs is also documented 28,40 .…”
mentioning
confidence: 99%
“…For the carbon‐based SACs, the metal centers usually coordinate with the N element in the first shell. However, other elements, such as S, Cl, and O, were also able to coordinate with center metals, which would affect the ECR performance 76,90,168,169 . Yang et al 103 reported the modification of an NG‐supported Ni SAC by S doping.…”
Section: Strategies For Optimization Of Ldm Supported Sacs For Ecrmentioning
confidence: 99%
“…However, other elements, such as S, Cl, and O, were also able to coordinate with center metals, which would affect the ECR performance. 76,90,168,169 Yang et al 103 Reproduced with permission. 89 Copyright 2019, Wiley-VCH.…”
Section: Engineering the Coordination Atommentioning
confidence: 99%